(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Our study had a double objective: to highlight the causal relationship between human capital and economic growth, and then identify which of its dimensions or quantitative measures perform better in explaining the influence on the income per capita in Romania. The conclusions after analyzing the results of econometric patterns estimates obtained make us see human capital as an important factor in economic increase, even if with certain specifications and measures of education we also obtained negative or inconclusive results.